HBeAg testing is better than quantitative HBsAg assay as an alternative to HBV DNA assay among HBV-infected pregnant women - Minh Ngoc Nguyen; Thi Thu Huong Nguyen; Tran Dieu Hien Pham; Van Nghia Khuu; Quoc Cuong Hoang; Vu Thuong Nguyen; Ngoc Huu Tran (Journal of Infection in Developing Countries)
Introduction: Using tenofovir disoproxil fumarate (TDF) is recommended in the 3rd trimester for pregnant women with HBV DNA ≥ 200,000 IU/mL to prevent mother-to-child transmission (MTCT) of hepatitis B virus (HBV). However, HBV DNA quantification is unavailable in many resource-limited areas worldwide, hence prophylaxis is often missed. The aim of this study was to determine whether HBeAg or qHBsAg is a better alternative to HBV DNA testing in HBV-infected pregnant women.